A Semantic Analysis of Taylor Swift's Songs: Leech's Seven Types Meaning - Kholilah Yuniar Nasution; Lismawarni; Mesra Sinambela; Dina Puspitra Sari Daulay (Insight School Academy, 2024)
Background: The abstract doesn't explicitly state a specific problem. It focuses on exploring the semantic richness of Taylor Swift's lyrics. Purpose: To identify and elucidate the different types of meaning embedded within Taylor Swift's song lyrics and understand how these meanings contribute to the overall emotional and thematic expression of the songs. Design/methods/approach: A descriptive qualitative approach, analyzing the lyrics of Taylor Swift's most popular songs based on Spotify records in 2024, using Geoffrey Leech’s theory of the seven types of meaning. Findings: Affective meaning is the most dominant type in Swift’s songs, In the song